Electronic Properties of Graphene Nanoribbons with Zigzag Armchair Edges (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied the electronic properties of graphene nanoribbons with zigzag armchair  edges. We have calculated the local density of states, the single particle special function, the  optical conductivity and the conductance for different geometries. We have also studied the  disordered effects. The influence of disorder on the transport behavior of tight binding  approach has been accepted. The conductance of edge contacted graphene nanoribbon  sensitivity was found dependent on the lead graphene nanoribbon matching conditions. In  this respect armchair graphene nanoribbon enabled a somewhat better current injection.  Dangling bonds on the graphene nanoribbon side of the interface substantially reduced the  conductance. The typical conductance of disordered graphene nanoribbons sandwiched  between graphene leads in a junction set up exhibited a negative differential conductivity  whenever new transport channels become available by increasing the Fermi level. This  accentuates the efficiency of Anderson localization function manifested a precursor of the  transition from a current carrying to an Anderson disorder induced insulating behavior which  takes place when the size of the disordered active graphene region becomes infinite. The  obtained results were found in good agreement with previously obtained results.